Recent Advances in Biocatalysis with Chemical Modification and Expanded Amino Acid Alphabet - Pagar, Amol D.; Patil, Mahesh D.; Flood, Dillon T.; Yoo, Tae Hyeon; Dawson, Philip E.; Yun, Hyungdon (Chemical Reviews, 2021)
The two main strategies for enzyme engineering, directed evolution and rational design, have found widespread applications in improving the intrinsic activities of proteins. Although numerous advances have been achieved using these ground-breaking methods, the limited chemical diversity of the biopolymers, restricted to the 20 canonical amino acids, hampers creation of novel enzymes that Nature has never made thus far. To address this, much research has been devoted to expanding the protein sequence space via chemical modifications and/or incorporation of noncanonical amino acids (ncAAs). This review provides a balanced discussion and critical evaluation of the applications, recent advances, and technical breakthroughs in biocatalysis for three approaches: (i) chemical modification of cAAs, (ii) incorporation of ncAAs, and (iii) chemical modification of incorporated ncAAs. Furthermore, the applications of these approaches and the result on the functional properties and mechanistic study of the enzymes are extensively reviewed. We also discuss the design of artificial enzymes and directed evolution strategies for enzymes with ncAAs incorporated. Finally, we discuss the current challenges and future perspectives for biocatalysis using the expanded amino acid alphabet.
Keywords: Artificial enzymes; Chemical diversity; Critical evaluation; Functional properties; Future perspectives; Intrinsic activities; Mechanistic studies; Non-canonical amino acids; Amino Acids; Biocatalysis; Glucosidases; Metalloproteins; Molecular Structure; Protein Engineering